(untitled) (Bangladesh Journal of Livestock Research, 2020)
The study was conducted in 13 upazilas from 850 Foot and Mouth Disease (FMD) affected households of four regions of Bangladesh during the period of July 2017 to June 2018. In all there were 4857 crossbred cattle and 2138 native cattle in the affected households. The crossbred and native cattle were grouped into three categories such as adult female, adult male and calf. The morbidity and mortality rates in crossbred cattle were 55.43%, and 5.15%, respectively and that rates in native cattle were 77.83% and 12.39%, respectively. Morbidity and mortality were found significantly higher in native cattle than in crossbred. Mortality of native calf was higher (21.27%) than in crossbred calf (9.50%). Seasonal influence of FMD was observed significantly higher in January- February (44.12%) and March-April (21.76%). There were a total of 248 pregnant cows infected in which abortion was reported in 26 (10.48%) cows. Besides this some clinical signs reported were lameness, mastitis and repeat breeding with incidences of 21, 12 and 43 cases, respectively. It was reported that 65.78% crossbred and 16.93% native cattle were vaccinated. Of the vaccinated crossbred cattle 78.37% were vaccinated by Department of Livestock Services (DLS) produced vaccine and 21.63% by imported vaccines. Vaccination cost per crossbred cattle by DLS vaccine was Tk. 49.49 and by imported vaccine Tk. 249. Disposal of dead cattle practices were left in open field, dropped into water, and buried were 17.63%, 52.87%, and 11.29%, respectively. Extrapolating the financial losses on 25.7 million cattle the annual financial losses due to FMD would be Tk. 188569.6 million (US 2220.82 million). Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 21-33